ANALISIS PENYEBAB WAKTU TUNGGU DARI PROSES ADMINISTRASI PEMULANGAN PASIEN RAWAT INAP DENGAN JAMINAN PRIBADI DI RUMAH SAKIT HERMINA DAAN MOGOT TAHUN 2019 - Yofa, Anis Septiana; Vionalita, Gisely (Health Publica, 2020)
AbstractThe standard according to the Ministry of Health for the speed of time providing information about inpatient bills is less than 2 hours. But in Hermina Daan Mogot Hospital has an average time in the administration process of returning patients with personal guarantees that is equal to 2 hours 48 minutes 27 seconds. This study aims to determine the cause of the non-achievement of standard time in the administrative process of returning the hospitalized patient with personal guarantees at Hermina Daan Mogot Hospital in 2019. This study uses a qualitative approach by conducting in-depth interviews, observation and document review. The informants of this study were 10 people. The results of this study affect the waiting time on the variables of the nursing process and inpatient pharmaceutical process, namely the number of human resources, IT systems, the number of patients resulting in the workload of nurses or pharmacy officers and the need for new policy making. In the medical support variable, there are no problems that can hamper the patient's discharge process. The administrative process variable is already said to be fast and good, but there is a cause for waiting time in the form of administrative queues in the nursing department due to the lack of human resources, lack of telephone facilities that are connected to the entire treatment room. Suggestions that can be given are in the form of fulfilling the number of human resources, especially in the pharmaceutical department, it is necessary to apply a good discharge planning, policy making in writing about medication management respontime especially in the inpatient pharmacy section, policy making or in writing about prevention for the input of advanced therapeutic drugs that are not as needed, the application of an IT information system that does not require inter-unit confirmation, job desc classification for administrative officers to treat patients with the same guarantee, and the addition of telephone units in the administration section connected to the treatment room.Keywords: Waiting Time, Administration Process, Patient Return, Personal Guarantee, Hospital.AbstrakStandar menurut Kemenkes untuk Kecepatan waktu pemberian informasi tentang tagihan pasien rawat inap yaitu kurang dari 2 jam. Namun di RS Hermina Daan Mogot memiliki rata-rata waktu dalam proses administrasi pemulangan pasien dengan jaminan pribadi yaitu sebesar 2 jam 48 menit 27 detik. Penelitian ini bertujuan untuk mengetahui penyebab ketidaktercapaian standar waktu dalam proses administrasi pemulangan pasien rawat inap dengan jaminan pribadi di rumah sakit Hermina Daan Mogot tahun 2019. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara mendalam, observasi dan telaah dokumen. Informan penelitian ini berjumlah 10 orang. Hasil penelitian ini yang mempengaruhi adanya waktu tunggu pada variabel proses keperawatan dan proses farmasi rawat inap yaitu jumlah SDM, sistem IT, jumlah pasien yang berakibat pada beban kerja perawat ataupun petugas farmasi dan perlunya pembuatan kebijakan baru. Pada variabel penunjang medik tidak ditemukan masalah yang dapat menghambat proses pemulangan pasien. Pada variabel proses administrasi sudah dikatakan cepat dan baik, namun terdapat penyebab waktu tunggu yaitu berupa antrian administrasi di bagian keperawatan yang disebabkan oleh kurangnya jumlah SDM, kurangnya sarana telepon ruangan yang terhubung dengan seluruh ruang perawatan. Saran yang dapat diberikan yaitu berupa pemenuhan jumlah SDM terutama pada bagian farmasi, diperlukan penerapan discharge planning yang baik, pembuatan kebijakan secara tertulis mengenai respontime pengelolaan obat khususnya di bagian farmasi rawat inap, pembuatan kebijakan atau secara tertulis mengenai pencegahan untuk penginputan obat terapi lanjutan yang tidak sesuai dengan kebutuhan, penerapan sistem IT informasi yang tidak memerlukan konfirmasi antar unit, klasifikasi job desc pada petugas administrasi untuk menangani pasien dengan satu jaminan yang sama, dan penambahan unit telepon di bagian administrasi yang terhubung dengan ruang perawatan.Kata kunci: Waktu Tunggu, Proses Administrasi, Pemulangan Pasien, Jaminan Pribadi, Rumah Sakit.